Post-mortem brain pathology is related to declining respiratory function in community-dwelling older adults - Buchman, Aron S.; Yu, Lei; Wilson, Robert S.; Dawe, Robert J.; VanderHorst, Veronique; Schneider, Julie A.; Bennett, David A. (Frontiers in Aging Neuroscience, 2015)
Damage to brain structures which constitute the distributed neural network that integrates respiratory muscle and pulmonary functions, can impair adequate ventilation and its volitional control. We tested the hypothesis that the level of brain pathology in older adults is associated with declining respiratory function measured during life.1,409 older adults had annual testing with spirometry and respiratory muscle strength based on maximal inspiratory and maximal expiratory pressures. Those who died underwent structured brain autopsy. On average, during 5 years of follow-up, spirometry and respiratory muscle strength showed progressive decline which was moderately correlated (ρ=0.57, p<0.001). Among decedents (N=447), indices of brain neuropathologies showed differential associations with declining spirometry and respiratory muscle strength. Nigral neuronal loss was associated with the person-specific decline in spirometry (Estimate, -0.016 unit/year, S.E. 0.006, p=0.009) and reduction of the slope variance was equal to 4%. By contrast, Alzheimer’s disease (AD) pathology (Estimate, -0.030 unit/year, S.E. 0.009, p<0.001) and macroscopic infarcts (-0.033 unit/year, S.E., 0.011, p=0.003) were associated with the person-specific decline in respiratory muscle strength and reduction of the slope variance was equal to 7%. These results suggest that brain pathology is associated with the rate of declining respiratory function in older adults.